Engaging with meditative inquiry in academia and beyond: A conversation - Kumar, Ashwani; Petersen, Bonnie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
In this conversational MJE Forum piece, Ashwani Kumar and Bonnie Petersen discuss the importance of meditative inquiry in academia and beyond. The primary focus of the conversation is Kumar’s new edited book, Engaging with Meditative Inquiry in Teaching, Learning, and Research: Realizing Transformative Potentials in Diverse Contexts. This book is a collection of chapters written by authors representing a wide range of perspectives, each discussing their own engagement with meditative inquiry. The conversation explores the underlying ideas behind Kumar’s meditative inquiry as an approach for learning and life, and the creation of the book.